2021
DOI: 10.1097/md.0000000000026702
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of persistent atrial fibrillation based on high density voltage mapping and complex fractionated atrial electrograms

Abstract: Introduction: Pulmonary vein isolation (PVI) is the cornerstone of atrial fibrillation (AF) catheter ablation. However, a PVI alone has been considered insufficient for persistent AF. This study aimed to evaluate the efficacy of persistent AF ablation targeting complex fractionated atrial electrogram (CFAE) areas within low voltage zones identified by high-resolution mapping in addition to the PVI.Methods: We randomized 50 patients (mean age 58.4 ± 9.5 years old, 86.0% males) with persistent AF to a PVI + CFAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…After screening, 52 studies were identified as potentially relevant, and their full-text manuscripts were carefully reviewed for possible inclusion. Finally, 16 articles fulfilled the inclusion criteria and were analyzed in our meta-analysis ( 9 , 13 15 , 21 32 ) ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening, 52 studies were identified as potentially relevant, and their full-text manuscripts were carefully reviewed for possible inclusion. Finally, 16 articles fulfilled the inclusion criteria and were analyzed in our meta-analysis ( 9 , 13 15 , 21 32 ) ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 1942 patients (mean age of 61 ± 10 years, 69% male) from 16 studies [six RCT ( 13 , 15 , 21 , 28 30 ), three prospective studies ( 9 , 23 , 26 ), and seven retrospective studies ( 14 , 22 , 24 , 25 , 27 , 31 , 32 )] were identified. The sample sizes ranged from 50 to 229, and the mean duration of follow-up was 18.9 months, ranging from 9.3 to 48 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex-fractionated atrial electrograms (CFAEs) are electrograms with highly fractionated potentials or with a very short cycle length (<120 ms), which represent potential AF substrate sites requiring ablation. The combination of CFAE ablation with high-density voltage mapping resulted in higher rates of freedom from AF compared to PVI alone [ 110 ]. Further documentation of CFAE ablation efficacy was present in another study, where the combination of PVI, CFAE, and linear ablation resulted in a greater freedom from atrial arrhythmia in comparison to sole PVI (HR 1.56, 95% CI 1.04–2.34) [ 111 ].…”
Section: Atrial Fibrillation Catheter Ablationmentioning
confidence: 99%